P632 Apical mass after acute myocardial infarction. (17th January 2020) - Jimenez Arjona, R; Cepas-Guillen, P; Doltra, A; Ortiz, J T; Vidal, B
Abstract: Funding Acknowledgements: No financial support 53-year-old male, with a personal history of high blood pressure and current smoking. He presented in the emergency department with typical chest pain. The initial electrocardiogram showed a ST segment elevation in DI and AVL leads. An emergency coronariography was performed showing a single vessel disease with two tandem lesions on the first diagonal, which were treated with pharmacoactive stents. An echocardiography was performed, showing a mild apicolateral hypokinesia, with good contractility of the remaing segments. In addition, a rounded, pediculated and mobile mass in the apex was observed; the mass was hyperechogenic compared to the myocardium. In this setting, the differential diagnosis should include thrombus in context of acute coronary syndrome (despite a small infarction with early revascularization and good contractility of the segments involved) vs. tumoral mass. Anticoagulant treatment was maintained and a cardiac magnetic resonance (MR) was performed. The MR showed an apical round mass of 11 mm, with hyperintense signal in both T1- and T2-enhanced sequences in comparison to normal myocardium; although no contrast uptake was observed in early gadolinium enhancement sequence, the mass showed homogeneous enhancement in the late enhancement images, both with optimal TI and with long T1. These findings were suggestive of a benign tumoral mass of atypical location. In addition, a small anterior subendocardial enhancement with preserved ejection fraction was observed. A control echocardiogram after 5 weeks of anticoagulant treatment showed no changes in either size or characteristics of the mass. After risk-benefit assessment and according to patient preferences, surgical resection of the mass was decided by a mini-thoracotomy approach. A surgical piece was obtained, described as a mobile pediculated tumour with a granulated surface and mucinous aspect. The postoperative period was uneventful. Subsequently, the pathological study confirmed the diagnosis of papillary fibroelastoma of atypical location. This case summarizes the usefulness of MR to characterize cardiac masses and, in particular, to differentiate tumours from thrombus. Although in this setting (recent myocardial infarction) an apical thrombus was initially suspected, the MR exam correctly identified a contrast enhanced mass, which ruled out acute thrombus and suggested benign tumour.